Comparison of shear wave splitting and finite strain from the India-Asia collision zone - Davis, P; England, P; Houseman, G (1997)
We investigate whether observations of shear wave splitting in Asia may be related to distributed strain of the lithosphere or to strain caused by motion of the Asian lithosphere over the deep mantle. The HS2-NUVEL angular velocity for Eurasia, and that of Minster and Jordan [1978], predict "absolute" plate motions that are a factor of at least 4 slower than the NNE relative motion of India with respect to stable Eurasia. Shear of the upper mantle beneath the south Asian lithosphere is therefore likely to be dominated by the velocity field caused by the internal deformation of Asia, rather than by plate motion. If that shear causes SKS splitting, fast polarization directions in tectonic Asia should be aligned approximately in the direction of the motion of Asian lithosphere relative to the deep mantle, which for southern Asia is NNE. In general, however, fast polarization directions are not aligned with this direction, and in some cases are nearly orthogonal to it. We calculate finite deformation of the Asian lithosphere, in response to its indentation by India and, from the deformation, predict the orientations of fast polarization directions aligned with the principal axes of elongation. These predictions agree with the gross features of the anisotropy in Tibet and the Tien Shan. Orientations of anisotropy in the Baikal region of Siberia are consistent with the orientations of the local principal axes of active strain. Orientations of anisotropy in Mongolia, however, are inconsistent both with the azimuth of the velocity of this region with respect to the deeper mantle and with the orientation of the calculated maximum elongation of the region. We conclude that SKS splitting observations from Asia agree better with those predicted by calculations of internal lithospheric deformation due to indentation by India than with strain predicted from motion of the lithosphere over the deeper mantle. These results place constraints on the depth range where shear wave splitting occurs, which we propose lies predominantly within the lithospheric mantle.